ENVIRONMENTAL CULTURED EDUCATION AND ITS IMPLICATION ON THE STUDENT’S COMPETENCIES IN AN ADIWIYATA SCHOOL - Siswanto Siswanto; Karimullah Karimullah; Reni Prasetyawati; Nurhayati Nurhayati (LPMPP Universitas Negeri Yogyakarta, 2019)
Destructive behavior towards nature adversely affects environmental damage. The root of this crisis lies in the structure of the value of human life in interacting with nature. This research aims at studying a philosophical foundation, model, aspect of environmental cultured education, and it’s implication on the student’s competencies in three schools. It employes phenomenology. Data were gained from deep-interview, observation, and document analysis. The information is determined with a purposive sampling technique. While data were analyzed descriptive-exploratively, involving data reduction, data display, and conclusions. This research finds that the vision and mission of the school become the main foundation in growing awareness of environmental cultured education. The model of environmental cultured education is developed integratively through all subjects. The aspect of education was formulated in the Adiwiyata programs dan Educotourism with participatory and sustainable principles. The implications for student competencies including demonstrating environmental cultured attitudes and behavior, the cognitive understanding of environmental education, and developing in own students’ skills, creativity, and productivity.